Todos entran, ¿todos juegan? : Políticas de inclusión en la FBA - Quiroga, Agustina (2017)
The Facultad de Bellas Artes (FBA) of the Universidad Nacional de La Plata (UNLP) has significantly increased the number of students in a context of public policies for university inclusion during the Kirchnerist government. The FBA took measures focused on strengthening educational trajectories. The Entre Pares program is one of these policies. Some of the inclusion actions developed in a massive faculty with a conception of education as a social right are presented.